LES study of the combined effects of groups of vortices generated by a pulsating turbulent plane jet impinging on a semi-cylinder. (5th March 2017) - Kharoua, Nabil; Khezzar, Lyes; Nemouchi, Zoubir; Alshehhi, Mohamed
Graphical abstract: Highlights: A heating pulsating plane jet impinging on a curved surface was studied by LES. A change in dominant frequency from 600 Hz to 300 Hz is observed at about s/W = 1. Heat transfer decreases within the growing laminar boundary layer for s/W < 2. Heat transfer decreases when cold air is drawn in by primary vortices for s/W > 2. Nu and Cf are no-longer-correlated when induced vortices are surrounded by cold air. Abstract: The present work is a numerical study of a submerged pulsating plane turbulent jet impinging on a convex semi-cylinder placed at a distance equal to twice the nozzle-exit width, using the Large Eddy Simulation approach. The temperature of the jet is higher than that of the surrounding air and the impingement wall. The Reynolds number, based on the nozzle-exit width and the time-averaged velocity is equal to 5600. The inflow is forced at a frequency of 600 Hz by imposing a sinusoidal velocity profile at the nozzle exit. The study focuses on the effects of the organized structures, shed from the free-shear layer, on the boundary layer developing along the curved surface and the corresponding heat transfer. In particular, the present contribution is an investigation, in an unexplored research field, namely, the simultaneous time-dependent responses of the Nusselt number, the friction coefficient and the pressure profiles to the passage of the coherent structures along the curved wall. The passage of the primary coherent vortices induces secondary vortices within the boundary layer and entrains both the hot air, from the jet, and the cold air, from the surroundings, which is undesirable in heating applications. The primary vortices, the induced vortices and their pairing have a major effect on the heat and fluid flow. Thus, air is entrained towards the wall immediately downstream of the induced vortices (downwash) and ejected away from the wall just upstream (upwash). It is shown that the dynamic field can be uncorrelated with the thermal field and may not be sufficient for a good prediction of the expected heat transfer.